The study on the relationship between venture capital, tolerance to failure, and enterprise innovation performance - Han, Jin; Chen, Minling; Chen, YanXin; Jing, Qinling; Wang, ShuangYan (Frontiers in Psychology, 2023)
As a new type of financing, venture capital plays an important role in enterprise innovation. It not only affects enterprise innovation decisions by providing funds, value-added services and allocating control rights, but also the psychological capital of venture capital can enhance its tolerance for failure in early innovation activities of enterprises, and thus have a positive impact on innovation performance of enterprises.This paper collects data on financing and innovation of listed companies, and uses multivariate and negative binomial regression models, propensity score matching method and Heckman treatment effect model to study the impact mechanism of venture capital on enterprise innovation performance, and the intermediary role of venture capital's tolerance for innovation failure in the relationship between the above two; this paper studies the moderating effect of the characteristics of heterogeneous venture capital institutions, such as joint investment strategies and geographical proximity, on the relationship between venture capital failure tolerance and enterprise innovation performance.The results show that venture capital can significantly improve its tolerance for enterprise innovation failure by holding shares and occupying seats on the board of directors of enterprises, thereby improving the innovation performance of enterprises; joint investment strategy and geographical proximity positively moderate the impact of venture capital failure tolerance on enterprise innovation performance. This paper not only reveals the mechanism of venture capital's influence on enterprise innovation performance by tolerating innovation failure, but also provides empirical evidence for establishing enterprise innovation tolerance culture and promoting enterprise scientific and technological innovation.